(untitled) (Research, Society and Development, 2024)
This article presents a systematic review that aimed to map the articulations between academic productions published in the proceedings from 2019 to 2023 of the National Meeting of Research in Science Education (ENPEC) and in the Digital Library of Theses and Dissertations (BDTD), in the period from 2018 to 2023, with the Base Nacional Comum Curricular (BNCC) with regard to fields of experience in Early Childhood Education. The study problem is: what alignments can be found between science education experiences carried out in Early Childhood Education and the BNCC propositions about fields of experience? A qualitative content analysis of these productions was used, after 82% of those published in ENPEC and 80% in BDTD were discarded because they focused on themes that are not directly related to the focus of this review. The thirty-two productions analyzed indicate that it is possible to draw alignments and articulations of methodological propositions with BNCC’s fields of experience. The results indicate that the BNCC’s alignments with the fields of experience are more evident: "Listening, Speaking, Thought and Imagination" and "Spaces, Times, Quantities, Relations and Transformations". pedagogical strategies that provide opportunities for children to take a leading role and spaces and experiences that mobilize children to think, speak and question.